Trading volume and volatility patterns across selected Central European stock markets from microstructural perspective - Gurgul, Henryk; Syrek, Robert (Managerial Economics, 2017)
In this paper, the intraday patterns of trading volumes and volatilities as well as autocorrelations are investigated using high-frequency data. The analysis is performed for companies listed in the main German, Austrian, and Polish indices with the aid of Flexible Fourier Form regression. We have found some similarities to prior investigations in light of stylized facts about intraday patterns. We noted the differences in intraday patterns and autocorrelations across markets, which depend on the maturity level of the market. The most-regular patterns are observed for DAX companies. Additionally, using day-of-the-week dummies, we discover some peaks that can be associated with macroeconomic announcements in Germany and the US. This leads to conclusions that the day of the week and announcements should be taken into account in modeling volatilities (returns) and volumes from high-frequency data.